2020
DOI: 10.1038/s41467-020-15768-x
|View full text |Cite
|
Sign up to set email alerts
|

Genomic landscape of platinum resistant and sensitive testicular cancers

Abstract: While most testicular germ cell tumours (TGCTs) exhibit exquisite sensitivity to platinum chemotherapy,~10% are platinum resistant. To gain insight into the underlying mechanisms, we undertake whole exome sequencing and copy number analysis in 40 tumours from 26 cases with platinum-resistant TGCT, and combine this with published genomic data on an additional 624 TGCTs. We integrate analyses for driver mutations, mutational burden, global, arm-level and focal copy number (CN) events, and SNV and CN signatures. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
88
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(96 citation statements)
references
References 63 publications
6
88
2
Order By: Relevance
“…Despite intense research efforts directed towards a better understanding of cisplatin sensitivity and resistance in this tumor model, a major unifying mechanism is still lacking which may be therapeutically targeted [ 10 , 11 , 12 , 13 ]. Most likely, the biology of cisplatin resistance is multifactorial [ 12 , 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Despite intense research efforts directed towards a better understanding of cisplatin sensitivity and resistance in this tumor model, a major unifying mechanism is still lacking which may be therapeutically targeted [ 10 , 11 , 12 , 13 ]. Most likely, the biology of cisplatin resistance is multifactorial [ 12 , 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Broad characterization of these refractory tumor cells and tissue samples in ongoing and future studies will be instrumental to pinpoint specific markers robust enough to predict the emergence of such resistant phenotypes, so that it can be anticipated and prevented. Furthermore, it will disclose biomarkers of response to alternative treatments (such as epigenetic-based ones) that can be combined with cisplatin and even rescue sensitivity to this drug [ 161 , 162 , 163 , 164 , 165 , 166 , 167 ]. In particular, biomarkers of sensitivity to immunotherapies could be envisioned to better select patients for these therapies and improve the results of recent trials [ 168 ].…”
Section: Future Directionsmentioning
confidence: 99%
“…Indeed, subtypes such as seminoma are particularly sensitive to DNA-damaging agents, while others such as yolk sac tumor appear frequently in the cisplatin-resistant metastatic context, reflecting differences in biology. Overall, studies on cisplatin resistance making use of such chemo-exposed patient samples are scarce [ 31 , 34 , 35 , 36 , 37 ], and researchers often turn their attention to primary tumors of patients known to have developed resistance in the future, which is suboptimal given their chemo-naïve constitution [ 15 ]. Additionally, there is great heterogeneity within mixed tumors, with the cisplatin-resistant metastatic histological component not always being the dominant clone within the primary tumor; this is another argument in favor of interrogating the metastatic tumor instead of the primary.…”
Section: Models For Studying Cisplatin Resistance Biologymentioning
confidence: 99%
“…Two recent studies, making use of cell line models made resistant to cisplatin or cisplatin-resistant TGCTs (primaries and metastases, the largest series so far on whole genome sequencing), demonstrated that a resistant disease depicted significantly more CNAs (such as losses of chromosomes 1, 4, and 18 and gains of chromosome 8); single nucleotide polymorphisms (SNPs); and higher tumor mutational burdens (TMBs) [ 15 , 37 ]. One study found alterations in genes already known to be involved in the risk of acquiring TGCTs ( DMRTA1 ), others on genes previously known to contribute to resistance ( MDM2, although the association was not confirmed on the second mentioned study [ 37 ]), and uncovered novel targets ( ATRX and NSD1 ) [ 15 ]. Both these new targets are of interest and reinforce the connection of cisplatin resistance with epigenetics (see above), as the former represents a chromatin remodeler (of the SWI/SNF family), and the latter constitutes a histone methyltransferase.…”
Section: Dissecting Cisplatin Resistance Mechanismsmentioning
confidence: 99%